Role of platelet-rich plasma in insertion tendinitis - Nibin Sunny,; Saurabh Agarwal,; Mahesh Navadaya,; Mayank Kumar Singh, (Asian Journal of Medical Sciences, 2024)
Background: Platelet-rich plasma (PRP) helps in the treatment of various insertion tendinitis, and the recurrence rate will be low. In this study, we used intralesional injections of autologous PRP for the treatment of insertion tendinitis. Aims and Objectives: Assessment of pain relief following PRP treatment for insertion tendinitis and ascertaining the efficacy of PRP as a treatment option for insertion tendinitis. Materials and Methods: The study was done at Maharani Laxmi Bai Medical College, Jhansi, between January 2021 and June 2022, including 100 patients were applied for the treatment of PRP. We assessed patients before treatment and at three follow-up time points: 2, 4, and 6 months after the end of treatment. During each evaluation, three parameters were noted: Victorian Institute of Sports Assessment- Achilles (VISA-A) score, the Visual Analog Scale, and patient satisfaction according to the roles and Maudsley score. Results: This was a prospective trial by study design conducted on 100 patients, which included 44 patients with plantar fasciitis and 56 patients with tennis elbow. The response to PRP injection in patients with plantar fasciitis was assessed by the VISA-A score. The pre-injection VISA-A score of patients with plantar fasciitis was 56.82 (mean with SD of 18.015), which improved to 65.45 in the 2nd month (mean with SD −18.857), 4th month with 69.77 (mean with SD–19.823), and at 6 months 71.82 (mean with SD–20.829). Statistical analysis with an analysis of variance test gave a P=0.001. In our study, the patients had gradual sequential improvement in VISA-A score throughout the follow-up, with maximum improvement from the pre-injection score were observed in 2 months (65.45 with SD 18.85). Conclusion: Autologous PRP injection is a safe and useful modality of treatment in the treatment of insertion tendinitis.